Intramuscular ganglionic cyst in the extensor digitorum longus muscle of the leg: A case report and review of literature - Ahmad, Javed; Ajeet Kumar Yadav; Brijmohan Patel; Vivek Kumar Shrivastava; Amit Kumar Rajan (Asian Journal of Medical Sciences, 2024)
Ganglionic cysts are benign soft-tissue lesions with unclear etiology and pathogenesis commonly occurring on the wrists and hands. Although their diagnosis and management in these characteristic locations are easy, rare occurrences in atypical locations are difficult to diagnose. Ultrasonography and magnetic resonance imaging (MRI) are helpful in diagnosing and differentiating a ganglionic cyst from other soft-tissue lesions. Here, we report a case of 60-year-old male patient with intramuscular ganglionic cyst, measuring 68×41×48 mm, arising in the extensor digitorum muscle of the left leg, which was diagnosed using MRI and treated using excision and biopsy.